Analysis Of Training, Provision Of Welfare And Implementation Of Position Promotions On Employee Performance At Rsu Royal Prima Medan - Ermi Girsang; Kriahan Joel Fieterson; Ali Napiah Nasution (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Hospitals play a crucial role in providing health services, and human resources are essential for their success. To ensure good human resources, organizations must assess employee performance and provide training, welfare, and job promotions. A study using systematic sampling and Proportional Random Sampling with 240 samples found that the majority of respondents were aged 31-40 years, female, with a bachelor's degree, and had worked less than five years. The study found a significant relationship between training, welfare provision, and job promotion implementation at RSU Royal Prima Medan. The most influential factor on employee performance was the implementation of job promotions. The research suggests that RSU Royal Prima Medan should provide periodic training to employees, provide welfare in line with their duties and responsibilities, and ensure transparent and compliant job promotion implementation. In the future, RSU Royal Prima Medan should focus on providing training to employees, providing welfare in line with their duties and responsibilities, and ensuring job promotions are carried out transparently and in accordance with applicable provisions.